Efeito de proteção de um composto de suplemento (multicafé®) em um modelo de estresse agudo por contenção - Moretto, Joana Grandó (2020)
The well-being of humans and animals is a topic that has become very important in the world, due to changes in habits. The animal's first level of response to a stressful or aversive environment is changing in behavioral and molecular patterns. So antioxidants and anti-inflammatories can be related to health benefits, the lack of treatment strategies makes daily customs as alternatives as a solution. Making functional foods move approximately $ 129 billion. The term "Stress" is used to describe a variety of physiological and/or psychological stimuli, which can have direct or indirect effects on body function. New studies appear intending to minimize these effects, as in the case, research with the compound MULTICAFÉ®, which is a completely natural food supplement to be obtained from roasted guarana seed powder, rice flour and Brazil nuts. The present study aimed to study possible biochemical and anxiolytic effects of this supplement in animal models subjected to acute stress due to space restriction. We evaluated the potential preventive effects of CM in the acute restriction stress (RAS) model in male Swuis mice (45 days). EAR was induced by individual confinement for two hours/day for ten days. The MC was administered orally 2.63 mg/day. The animals were submitted to behavioral anxiety and biochemical tests such as reactive oxygen species (ROS) and total content of non-protein thiols, lipoperoxidation, total antioxidant capacity (TAC), activities of the enzymes catalase and acetylcholinesterase. We observed that EAR increased the production of EROs, AChE, CAT activities in the liver, kidney. On the other hand, the MC was able to attenuate most of these elevations, decreasing the reactive species, mainly in the liver and kidney tissues, and restoring the balance of the antioxidant activity evaluated by T-SH in the brain and kidney organs, in addition, the MC showed an increase in kidney TAC. Finally, MC has a promising future, since it is easily produced through natural substances and its antioxidant effects can be a new all-natural alternative for changes in stress-related health losses.